Drought-induced expression of PvDERB1F and PvDREB5A with promoted antioxidant activities possibly enhanced drought stress tolerance in Common bean (Phaseolus vulgaris L.) - Motlalepula Pholo-Tait; Lekgari Lekgari; Moagisi Ithuteng (Acta Agriculturae Slovenica)
The integration of Phaseolus vulgaris L. as a priority crop in a diversified farming system is paramount for its social, environmental and economic benefits. Despite drought stress being one of the major crop production limiting factors in Botswana, much research has been focused on yield stability under rainfed conditions. In that regard, performance under drought stress and molecular mechanisms aligned to morphological performances remain unclear. Transcriptional, enzymatic and non-enzymatic antioxidative analyses were performed to evaluate the performance of common bean genotypes under drought stress. The study highlights CAL96 and DAB541 genotypes as the most promising drought tolerance genotypes due to biomass production under drought stress. The increase or maintained biomass production was possibly attributed to overexpression of PvDREB1F and PvDREB5A genes, enhanced accumulation of proline and a substantial reduction in MDA content. Furthermore, these positively correlated with an increase in CAT and APX-associated H₂O₂ scavenging activity. Inversely, the inhibited dry biomass, decrease in the expression of PvDREB1F, PvDREB5A, and PvDREB6B with greater levels of MDA and H₂O₂ and a steady activity of APX and CAT were observed in GK011 and DAB514. This suggested disequilibrium with a consequential enhanced membrane lipid peroxidation and a loss of membrane integrity.